Zamenjava - Jesse, Staško (Arheološki vestnik, 1957)
The archaeological Section of the Slovene Academy of Sciences and Arts exchanges its archaeological publications.
Keywords: archaeology; arheologija; exchange of publications; indexes; scientific institutions; seznami; zamenjava publikacij; znanstvene ustanove